Analisis Tingkat Intensitas Kebisingan terhadap Kelelahan Kerja Karyawan Bagian Produksi PT Sinar Sosro Palembang - Rahmi Garmini; Rio Purnama (Poltekkes Kemenkes Yogyakarta, 2020)
Occupational fatigue will increase the level of work errors and reduce performance or producti- vity. If work errors increase, there will be opportunities for workplace accidents in the industry. The purpose of this study was to determine the analysis of noise level intensity on occupational fatigue among workers at PT Sinar Sosro Palembang. The research method uses total sampling or the entire population as the study sample i.e. 40 workers of production unit. The study results obtained p-value of 0,864, which means there is no relationship between the level of noise and work fatigue among production unit workers. Nonetheless, the workers who experience mild and medium fatigue are recommended to take a short break for 5-15 minutes every 1 to 2 hours and it is expected for employees to comply more fully with PPE regulations in order to avoid work accidents.